Distribution of Blood Groups among Biology Education Students at FKIP, University of Mataram, Academic Year 2023/2024 - I Wayan Merta; Kusmiyati Kusmiyati (Jurnal Biologi Tropis, 2026)
A study entitled Blood Group Characteristics of Students of the Biology Education Study Program, FKIP, University of Mataram, Class of 2023/2024 has been conducted. This study aimed to: (1) determine the characteristics of blood groups among students of the Biology Education Study Program, FKIP, University of Mataram, class of 2023/2024; and (2) enhance students’ understanding in the Human Anatomy and Physiology course, particularly regarding blood groups. The determination of blood groups is crucial in the medical field, as incompatibility between donor and recipient blood groups during transfusion can trigger serious immune reactions, such as hemolysis, anaphylactic shock, and even death. This research employed a descriptive, non-experimental design, in which the researchers collected basic information on students’ blood groups without conducting laboratory examinations. Data were collected online using Google Forms as the primary instrument. Based on the research results, the distribution of blood groups was as follows: O = 49.22% (63 students), B = 28.91% (37 students), A = 18.75% (24 students), and AB = 3.13% (4 students). It can be concluded that the blood group distribution among Biology Education students of the 2023/2024 cohort shows a dominant pattern of blood group O. Out of a total of 128 respondents, blood group O accounted for 49.22% (63 students), followed by blood group B at 28.91% (37 students), blood group A at 18.75% (24 students), and blood group AB at 3.13% (4 students).